Manufacturing Technics for Fabric/Fiber-Based Triboelectric Nanogenerators: From Yarns to Micro-Nanofibers - Chonghui Fan; Yuxin Zhang; Shiqin Liao; Min Zhao; Pengfei Lv; Qufu Wei (Nanomaterials, 2022)
Triboelectric nanogenerator (TENG), as a green energy harvesting technology, has aroused tremendous interest across many fields, such as wearable electronics, implanted electronic devices, and human-machine interfaces. Fabric and fiber-structured materials are excellent candidates for TENG materials due to their inherent flexibility, low cost, and high wearing comfort. Consequently, it is crucial to combine TENG with fabric/fiber materials to simultaneously leverage their mechanical energy harvesting and wearability advantages. In this review, the structure and fundamentals of TENG are briefly explained, followed by the introduction of three distinct methods for preparing fabric/fiber structures: spinning and weaving, wet spinning, and electrospinning. In the meantime, their applications have been discussed, focusing primarily on energy harvesting and wearable self-powered sensors. Finally, we discussed the future and challenges of fabric and fiber-based TENGs.